(untitled) (Modern education and development, 2025)
Marketing is a set of market analysis tools (such as sales forecasting methods, market simulation models, and surveys) that are only available to large enterprises and are used to develop a forward-looking and scientific approach to analyzing needs and demands. Marketing is a market system in which buyers exploit consumers commercially.